Metabolomic and transcriptomic analyses reveal response mechanisms of juvenile flounder (Paralichthys olivaceus) to sublethal methylmercury - Ren, Zhonghua; Ning, Junhao; Cao, Liang; Liu, Jinhu; Zhan, Junfei; Wang, Zhikang; Yu, Junbao; Yang, Jisong; Lv, Zhenbo (Frontiers in Marine Science, 2022)
Although methylmercury (MeHg) has been recognized as a typical heavy metal posing huge damages to various life processes of fish, the response mechanisms of marine fish at early life stages (ELSs) to MeHg is still poorly understood. In this study, non-targeted liquid chromatography-mass spectrometry (LC-MS) based metabolomic and transcriptomic approaches were used to explore response mechanisms of juvenile flounder (Paralichthys olivaceus) to long-term sublethal MeHg exposure (0 and 1.0 μg L-1; 30 d). After exposure, growth parameters of flounder were significantly decreased. Metabolomic and transcriptomic analyses of liver tissue showed obvious difference about biological pathways and identified biomarkers (around 2502 genes and 16 secondary metabolites). Those significantly differentially expressed genes (DEGs) and their enriched pathways were mainly related to immune response, oxidative stress, lipids metabolism, glycometabolism, amino acid and nucleotide metabolism and regulation of protein processes, while those identified secondary metabolites were mainly enriched in tryptophan metabolism, biosynthesis of unsaturated fatty acids, linoleic acid metabolism and glutathione metabolism. Additionally, multi-omic method was used to explore response mechanisms of key pathways under MeHg stress. In this regard, only 57 DEGs and 6 secondary metabolites were significantly enriched in 7 pathways to constitute an integrated regulatory network, including glutathione metabolism, thyroid hormone synthesis, linoleic acid metabolism, biosynthesis of unsaturated fatty acids, tryptophan metabolism pathway, serotonergic synapse and African trypanosomiasis. Above all, we could speculate that antioxidative function, lipids metabolism, nervous system and amino acid metabolism were the more sensitive targets in response to MeHg stress, which were conductive to deeply understand the response mechanisms of fish at ELSs under MeHg exposure. Those identified biomarkers could also be widely used for toxicological studies of pollutants and ecological risks monitoring.